2004
DOI: 10.1007/s00125-003-1296-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of autoimmune diabetes in glutamic acid decarboxylase 65 (GAD65) knockout NOD mice

Abstract: Aims/hypothesis. Type 1 diabetes mellitus, a T-cellmediated autoimmune disease, results from the selective destruction of insulin-producing pancreatic beta cells. Autoantibodies against beta-cell components are used clinically as sensitive markers of this disease; however, their physiological role has not been clear. To investigate the role of glutamic acid decarboxylase 65 (GAD65) in the development of the Type 1 diabetes of non-obese diabetic (NOD) mice, we analysed and characterised NOD mice with targeted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 10 publications
1
45
0
Order By: Relevance
“…Knockout of both Ins1 and Ins2, with restoration of hormonal function by transgenic expression of insulin, with an inactivated CD4 and CD8 epitope, completely prevents the development of antiinsulin antibodies, insulitis, and diabetes [44]. Knockouts of GAD65 or IA-2 expression does not alter diabetes onset in NOD mice [45,46]. These findings are consistent with the hypothesis that proinsulin is the primary antigen that initiates disease.…”
Section: Insulin Is the Primary Antigen In Nod Micesupporting
confidence: 81%
“…Knockout of both Ins1 and Ins2, with restoration of hormonal function by transgenic expression of insulin, with an inactivated CD4 and CD8 epitope, completely prevents the development of antiinsulin antibodies, insulitis, and diabetes [44]. Knockouts of GAD65 or IA-2 expression does not alter diabetes onset in NOD mice [45,46]. These findings are consistent with the hypothesis that proinsulin is the primary antigen that initiates disease.…”
Section: Insulin Is the Primary Antigen In Nod Micesupporting
confidence: 81%
“…At the fifth generation (F5), mice were screened for polymorphic microsatellite markers to determine whether they had the NOD gene background and we confirmed that they had NOD type on all markers shown in the electronic supplementary material (ESM) Fig. 1 [17]. Cxcr3 homozygous knockout female NOD mice were generated by crossing F6 knockout male and heterozygous female mice (speed congenic method).…”
Section: Animalsmentioning
confidence: 90%
“…05-71) and were performed according to the Guide for Care and Use of Laboratory Animals (Institute of Laboratory Animal Resources, 1996). The generation of GAD65(Ϫ/Ϫ) mice has been described previously (Yanagawa et al, 1999;Yamamoto et al, 2004). These GAD65(Ϫ/Ϫ) mice were backcrossed to C57BL/6 mice more than 10 times, and then they were used for our experiments.…”
Section: Methodsmentioning
confidence: 99%